Two Disaccharide-Bearing Polyethers, K-41B and K-41Bm, Potently Inhibit HIV-1 via Mechanisms Different from That of Their Precursor Polyether, K-41A - Jie Liu; Qiuyu Wei; Xin Liu; Jiang Chen; Yujie Zhan; Qinglian Li; Qian Wang; Bingyu Liang; Junjun Jiang; Fengxiang Qin; Zongxiang Yuan; Qiuzhen Qin; et al. (Current Issues in Molecular Biology)
The screening of novel antiviral agents from marine microorganisms is an important strategy for new drug development. Our previous study found that polyether K-41A and its analog K-41Am, derived from a marine Streptomyces strain, exhibit anti-HIV activity by suppressing the activities of HIV-1 reverse transcriptase (RT) and its integrase (IN). Among the K-41A derivatives, two disaccharide-bearing polyethers—K-41B and K-41Bm—were found to have potent anti-HIV-1IIIB activity in vitro. This study aimed to clarify whether K-41B and K-41Bm have inhibitory effects on different HIV-1 strains or whether these two derivatives have mechanisms of action different from that of their precursor, K-41A. An anti-HIV-1 assay indicated that K-41B and K-41Bm have potent anti-HIV-1BaL activity, with low 50% inhibitory concentrations (IC50s) (0.076 and 0.208 μM, respectively) and high selective indexes (SIs) (58.829 and 31.938, respectively) in the peripheral blood mononuclear cell (PBMC)-HIV-1BaL system. The time-of-addition (TOA) assay indicated that K-41B and K-41Bm may exert antiviral effects by activating multiple stages of HIV-1 replication. A cell protection assay indicated that the pretreatment of cells with K-41B or K-41Bm has almost no inhibitory effect on HIV-1 infection. A virus inactivation assay indicated that pretreatment of the virus with K-41B or K-41Bm inhibits HIV-1 infection by 60%. A cell–cell fusion assay showed that K-41B and K-41Bm blocked the cell fusion mediated by viral envelope proteins. The HIV-1 key enzyme experiment also indicated that both compounds have certain inhibitory effects on HIV-1 IN. Furthermore, molecular docking showed that K-41B and K-41Bm interact with several viral and host proteins, including HIV-1 IN, an envelope protein (gp120), a transmembrane protein (gp41), and cell surface receptors (CD4, CCR5, and CXCR4). Overall, in addition to having a similar anti-HIV-1 mechanism of inhibiting HIV-1 IN like the precursor polyether K-41A, the disaccharide-bearing polyether derivatives K-41B and K-41Bm may also inhibit viral entry. This suggests that they display anti-HIV-1 mechanisms that are different from those of their precursor polyethers.